Laboratory validation of steady-state-transient test to determine relative permeability and capillary pressure. (1st August 2022) - Hemmati, N.; Borazjani, S.; Yang, S.; Badalyan, A.; Genolet, L.; Behr, A.; Zeinijahromi, A.; Bedrikovetsky, P.
Graphical abstract: Highlights: Determination of both relative permeability and capillary pressure from corefloods. Lab validation of steady-state transition test by secondary and tertiary imbibitions. Method validity is proven by close match for steady-state and continuous injections. Match of pressure-drop data is significantly more accurate than that for saturation. Concentric-circle distributor yields much less 3D effects than half-moon distributor. Abstract: The work aims at the laboratory validation and practical implementation of the steady-state-transient method for simultaneous determination of relative permeability Kr and capillary pressure Pc, which uses steady-state data along with the transient data between the steady states. A new methodology for preliminary choice of Kr and Pc and the detailed test modelling yields planning and design of the steady-state-transient test SSTT – the definition of admissible flow rate, number of steady states and injected water fractions, frequency and volumes of the effluent samples. The test-parameter choice is based on the newly derived theoretical criteria for validity of the model for two-phase flow in porous media, and the operational criteria for the accuracy of the measurements. The preliminary modelling also allows determining the type curves for transient pressure-drop histories, which are used to approximate the measured data and input the inverse solver. Two laboratory SSTTs with inlet half-moon and concentric-circle distributors are carried out. The agreement between the matched-modelling and experimental data for pressure-drop is significantly higher than for average saturation for both tests. The agreement for the test with the concentric-circle distributor is significantly closer than that of the half-moon distributor. This is explained by non-uniform saturation distributions in core cross-sections due to 3D flow, which is more pronounced in the case of half-moon distributor.